Peran dewan pengawas Syariah dalam meningkatkan pengeluaran zakat Bank Umum Syariah di Indonesia - Sunarsih, Uun; Dahlifah, Dahlifah (Jurnal STEI Ekonomi, 2023)
This research aims to test the influence of profitability, firm size, and inflation on zakat expenditure and test the Sharia Supervisory Board (DPS) moderating profitability, firm size, and inflation on zakat expenditure. This research is explanatory research with a quantitative approach. The research population is Sharia Commercial Banks (BUS) in Indonesia, listed on the Indonesia Stock Exchange for 2017-2022, and 14 BUS were obtained. This test uses SEM-PLS. The research results prove that profitability has no effect. Zakat may be a personal matter, not a company matter. Firm size has an influence; the greater the assets owned, the greater the potential for issuing zakat. Inflation has no effect because decreasing people's purchasing power will affect paying zakat. DPS does not moderate profitability because the company has yet to issue a fatwa on zakat. DPS can moderate firm size, meaning that DPS has carried out its role. DPS cannot moderate inflation, meaning that DPS must provide management with a good understanding that if they have reached the nisab and haul, they must issue zakat. Novelty in this research is adding a moderating variable and using Shariah Enterprise Theory.